Pembelajaran Partisipatif melalui Diskusi Kelompok untuk Meningkatkan Pengetahuan Kesehatan Gigi pada Siswa Sekolah Dasar - Jumriani Jumriani; Ira Liasari; R. Ardian Priyambodo; Siti Adlinah Fatman; Nur Afifah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2026)
Oral and dental health is an important component of children's overall health that supports quality of life and learning processes at school. A low level of knowledge regarding dental health may increase the risk of various oral and dental health problems. This study aimed to determine the effectiveness of dental health education using the group discussion method on the knowledge level of students at SD Inpres Mallengkeri 2 Makassar. This study employed a quantitative method with a One Group Pretest-Posttest Design experimental approach. The sample consisted of 53 sixth-grade students selected using the total sampling technique. Data were collected using a questionnaire consisting of 15 multiple-choice questions on oral and dental health administered before (pretest) and after (posttest) the dental health education intervention through the group discussion method. Data were analyzed using univariate and bivariate analyses with the Wilcoxon Signed-Ranks test. The results showed that before the intervention, most respondents had poor knowledge (52.8%), moderate knowledge (37.7%), and good knowledge (9.4%). After the intervention, most respondents were in the good knowledge category (94.3%) and moderate category (5.7%), with no respondents remaining in the poor category. The mean knowledge score increased from 57.42 ± 13.71 to 92.74 ± 9.28, representing a 61.51% improvement. The Wilcoxon Signed-Ranks test showed a p-value < 0.001, indicating a statistically significant difference between knowledge levels before and after the intervention. It was concluded that dental health education using the group discussion method was effective in improving the knowledge level of students at SD Inpres Mallengkeri 2 Makassar.